2023
DOI: 10.1007/s11701-023-01559-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted pyeloplasty in children: a systematic review of the literature

Abstract: Robotic pyeloplasty has become a natural progression from the development of open, then laparoscopic procedures to treat pediatric patients with ureteropelvic junction obstruction (UPJO). Robotic-assisted pyeloplasty (RALP) is now considered a new gold standard in pediatric MIS. A systematic review of the literature retrieved from PubMed and published in the last 10 years (2012–2022) was performed. This review underlines that in all children except the smallest infants, where the open procedure has benefits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Robotic platforms provide enhanced visualization and dexterity, enabling surgeons to perform intricate tasks with greater precision, reducing the risk of complications and improving outcomes. The minimally invasive nature of robotic-assisted procedures is particularly beneficial for pediatric patients, promoting a faster recovery and minimizing postoperative discomfort [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robotic platforms provide enhanced visualization and dexterity, enabling surgeons to perform intricate tasks with greater precision, reducing the risk of complications and improving outcomes. The minimally invasive nature of robotic-assisted procedures is particularly beneficial for pediatric patients, promoting a faster recovery and minimizing postoperative discomfort [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These modules may include gastrointestinal, thoracic, or neurological surgeries, tailoring the training to the diverse needs of pediatric and neonatal patients. Additionally, workshops focusing on adapting robotic techniques to specific anatomical challenges in younger populations contribute to a more holistic skill set [ 36 , 37 ].…”
Section: Costs Maintenance and Feasibility Of Robotic-assisted Surgic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate of pediatric RALP ranges from 90% to 100% ( 2 , 4 , 5 , 7 ). The largest single-institution study revealed a success rate of 96% and a reoperation rate of 3% ( 14 16 ). The success rate in our study is 97.8%, with a reoperation rate of 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, robotic surgery has better ergonomics that helps alleviate the fatigue of surgeons during surgery. Fifth, performing the refined operation in a limited space reduces secondary injuries (6,(14)(15)(16)(17). Finally, the learning curve of robot surgery is short, and is significantly shorter in surgeons with considerable LP experience.…”
Section: Discussionmentioning
confidence: 99%